Study Of Factors Involved In Perforative Peritonitis And Its Significance To Mortality And Morbidity (International Journal of Food and Nutritional Sciences, 2022)
Peritonitis caused by gastrointestinal perforation is one of the most prevalent surgical emergencies worldwide. Early detection and treatment of Perforation Peritonitis may significantly minimise morbidity and death. The result is improved by surgical treatment and good perioperative care. Nowadays, conservative trials have minimal function in perforation peritonitis.Extremes of age, delayed presentation, distal GI (colonic) perforation, comorbidities, sepsis, faecal peritonitis, and other factors all enhance mortality. Careful clinical examination and post-operative assessment aid in the stratification of high-risk patients in order to offer better treatment for them. (1-2) Peritonitis is a surgical emergency that necessitates patient resuscitation, laparotomy and peritoneal toilet insertion, omental patch application, and, in certain cases, surgery for ulcer management. (3-4) It has been well documented that the majority of perforated peritonitis patients in our subcontinent appear late. Typically, these patients have well-established widespread peritonitis with purulent faecal pollution and septicaemia, increasing the risk of morbidity and death and complicating the challenge of providing appropriate perioperative care. (4)